Hybrid artificial neural network and gravitational search algorithm in intrusion detection system - Rahati, Shahdokht, 1982-; Anazida Zainal, supervisor; Fakulti Komputeran (2013)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2013